Physical characteristics of elite adolescent female basketball players and their relationship to match performance - Fort-Vanmeerhaeghe, A.; Montalvo, A.; Latinjak, A.; Unnithan, V. (Journal of Human Kinetics, 2016)
There were two aims of this study: first, to investigate physical fitness and match performance differences between under-16 (U16) and under-18 (U18) female basketball players, and second, to evaluate the relationship between physical fitness and game-related performances. Twenty-three young, female, elite Spanish basketball players (16.2 1.2 years) participated in the study. The sample was divided into two groups: U16 and U18 players. The average scores from pre- and post-season physical fitness measurements were used for subsequent analyses. Anthropometric variables were also measured. To evaluate game performance, game-related statistics, including the number of games and minutes played, points, rebounds, assists, steals and blocks per game, were recorded for every competitive match in one season. When anthropometric and physical performance variables were compared between groups, the U18 group demonstrated significantly (p<0.05) higher values in upper (+21.2%) and lower (+27.11%) limb strength compared to the U16 group. Furthermore, no significant differences between groups were observed in match performance outcomes. Only two performance variables, steals and assists per game, correlated significantly with jump capacity, speed, agility, anaerobic power, repeated sprint ability and aerobic power (p = 0.005). These findings can help optimize training programs for young, elite female basketball players.